Association of T Stage and Serum CEA Levels in Determining Survival of Rectal Cancer - Wu, Shengwen; Gu, Wenlong (Frontiers in Medicine, 2020)
Purpose: To investigate the association of T stage and serum carcinoembryonic antigen (CEA) levels (C0 and C1) in determining oncologic outcomes of rectal cancer. Methods: Patients diagnosed with stage I-II rectal cancer patients were identified from the Surveillance, Epidemiology and End Results database. Results: In stage T1 disease, elevated level of serum CEA (C1) was associated with 227.6% increased risk of mortality compared to normal level of serum CEA (C0; HR = 3.276, 95%CI = 2.781 to 3.858, P < 0.001). Conclusions: Stage T1 rectal cancer, when involved in preoperative serum CEA elevation, may be a surrogate of biologically aggressive disease and correlate with unfavorable oncologic outcomes. Moreover, this subgroup of rectal cancer deserves more clinical attention of oncologists.